The return of tarzan, with ebook eaudiobook - Burroughs, Edgar Rice (Tarzan, 2009)
Tarzan had renounced his right to the woman he loved, and civilization held no pleasure for him. After a brief and harrowing period among men, he turned back to the African jungle where he had grown to manhood. It was there he first heart of Opar, the city of gold, left over from fabled Atlantis. It was a city of hideous men—and of beautiful, savage women, over whom reigned La, high priestess of the Flaming God. Its altars were stained with the blood of many sacrifices. Unheeding of the dangers, Tarzan led a band of savage warriors toward the ancient crypts and the more ancient evil of Opar.